More exposure to medical injury news, better doctor-patient communication, but less doctors' professional identity: A moderated chain mediation model - Li, Qiwei; Zhou, Jie; Chen, Lei (Frontiers in Public Health, 2022)
Objectives: In recent years, news of medical malignant injury events has become common in China. However, it is unclear how exposure to this news affects medical staff. Methods: The present study collected data from a sample of 311 medical staff in China. It explored the effect of exposure to such news on medical staff’s communication and willingness to let their children be doctors, which was an attitude that reflects their professional identity well. In addition, this study also examined the mediating roles of outgroup attribution and anxiety, and the moderating role of social support. Results: The results showed that exposure to news of medical injury could positively and directly predict the quality of doctor-patient communication, but negatively and indirectly predict medical staff’s willingness to let their children become doctors. These effects existed through the mediating role of anxiety and the chain mediating role of both outgroup attribution and anxiety. In addition, social support could mitigate the negative correlation between news exposure and outgroup attribution. Conclusions: These results suggest that news of medical malignant injury events may incentivize medical staff to improve the quality of communication in the short term, but it is not conducive to medical staff’s long-term mental health. That is, exposure to news of medical injury is likely to lead to a negative influence on their professional identity, although social support can alleviate this negative influence.